Tasybih Dalam Ilmu Balaghah: Balaghah - Ali, Muhammad Khalis (Program Studi Bahasa dan Sastra Arab STAIN Majene, 2023)
This article examines the concept In Tashbih study in al-Balaghah Science. This article uses a bibliography writing methodology using descriptive analysis methods, namely collecting data, compiling or clarifying, compiling and interpreting. In Balaghah, 3 major themes are found, namely Bayan, Maani, and Badi' knowledge. However, the object of this study is bayan science. Balaghah experts agree that the study of bayan science includes three things, namely Tasybih, Majaz and Kinayah. Tasybih is one branch of the discussion of Balaghah science in which there are explanations and parables. Tashbih is the first step to explain a meaning and a means to explain characteristics. With tashbih, we can increase the height of the meaning and its clarity and can make the meaning look more beautiful.